2011
DOI: 10.1111/j.1540-6210.2011.02464.x
|View full text |Cite
|
Sign up to set email alerts
|

Federalist No. 44: What Is the Role of Intergovernmental Relations in Federalism?

Abstract: Federalist No. 44 examines the connective mechanisms underlying a federal system of government. Traditionally called "intergovernmental relations," these systems were intended to facilitate the pursuit of eff ective implementation of national policies. Th is essay suggests that the national government's offi cers should not be impressed by collaboration unless it produces better performance or lower costs. Collaboration is a means to an end, not an absolute requirement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…It is suggested that the private sector and civil society organizations (CSOs) begin to play an important role in building public awareness. They help in overcoming political divisions that might constrain collective responses to major policy challenges (Agranoff, 2011; Davenport and Prusak, 2000; Puppim de Oliveira et al , 2021). The current COVID-19 pandemic is an example of acute external cause of organizational crisis.…”
Section: Methodsmentioning
confidence: 99%
“…It is suggested that the private sector and civil society organizations (CSOs) begin to play an important role in building public awareness. They help in overcoming political divisions that might constrain collective responses to major policy challenges (Agranoff, 2011; Davenport and Prusak, 2000; Puppim de Oliveira et al , 2021). The current COVID-19 pandemic is an example of acute external cause of organizational crisis.…”
Section: Methodsmentioning
confidence: 99%
“…Arguably, designers were more concerned with democratic rights and arrangements among institutions to protect these compared to matters of performance and issues involving coordination and responsibilities in intergovernmental relations. Yet, public policies and state responses to crises and other issues have become increasingly dependent on how well different levels of government work together (Puppim de Oliveira et al 2021; Agranoff 2011). Key decision‐making authorities and processes for solving policy problems that require a high level of coordination and expediency are seldom sufficiently established in either law or practice; instead, intergovernmental relations have often been caught up in issues such as fiscal governance and, in recent years, recentralization and political polarization (Conlan 2017; de Mello and Jalles 2020).…”
Section: Flaws In Late Democracies Exposed: the Case Of Brazilmentioning
confidence: 99%
“…Especially since the announcement of the transformational devolution plan in 2000 for the precision of the federal and provincial government's rules of responsibilities (Ahmad & Akif, 2007 ). It further empirically analyzed that this plan or reform significantly impacted the institutional quality for public services outcomes, resulting from coordination among federal and provincial governments (Agranoff, 2011 ; Aslam & Yilmaz, 2011 ). It further explored that devolution or delegation of political power will help construct a strong constitution of Pakistan and develop a robust regional bonding among provinces (Myerson, 2014 ).…”
Section: Research Backgroundmentioning
confidence: 99%